KorPatBERT 기반 CPC 분류 모델을 활용한 한국어 특허 문헌 검색 모델 성능 향상 연구 - 민재옥; Jaeok Min; 노한성; Hansung Noh; 곽민학; Minhak Kwak; 황솔빈; Solbin Hwang; 김태훈; Taehoon Kim (지식재산연구, 2025)
전 세계적으로 기술 패권을 둘러싼 경쟁이 날로 심화되고 있으며, 각국은 특허 확보를 통해 기술 우위를 확보하려는 노력을 강화하고 있다. 이 과정에서 신속하고 정확한 특허 검색은 국가 기술 주권 확립과 글로벌 경쟁력 강화를 위한 핵심 요소이다. 그러나 방대한 특허 데이터 속에서 선행 기술을 효과적이고 정밀하게 찾아내는 일은 여전히 도전적인 과제로 남아 있으며, 이를 해결하기 위해, 본 연구는 인공지능 기술을 활용한 고도화된 특허 검색 모델을 제안하였다. 본 연구는 방대한 특허 데이터를 사전 학습하여 특허 문헌의 세부적인 기술적 맥락을 깊이 이해할 수 있는 KorPatBERT 기반 CPC 분류 체계별 모델을 생성하는 방법을 제시하였다. 아울러, 이 모델을 통해 특허 문헌의 기술적 주제와 맥락을 효과적으로 반영하는 고차원의 문헌 임베딩 벡터를 생성하는 방법을 제시하였고, 대량의 특허 데이터를 실시간으로 처리할 수 있는 검색 시스템 구축 방법을 함께 제시하였다. 이를 통해 제안된 특허 검색 모델은 시스템과 결합하여 객관적인 성능 평가에서 기존 방식보다 개선된 검색 성능을 성공적으로 입증하였다. 본 연구에서는 현재 운영 중인 특허 검색 데이터 및 검색 시스템의 프로세스를 적용함으로써 산업적 활용성과 실질적 유용 가능성을 높이는데 기여하였다. 이러한 연구 결과는 국가와 기업이 지속적으로 혁신을 선도하고, 특허를 효율적으로 관리하고 활용할 수 있는 기반을 제공할 것으로 기대한다. The global competition for technological supremacy is intensifying, prompting every country to focus on securing technological advantages through patent acquisition. In this environment, efficient and accurate patent searching is a key factor for establishing national technological sovereignty and strengthening global competitiveness. However, identifying prior art patents accurately and effectively within vast patent data remains a challenging task. To address this challenge, this study proposes an advanced patent search model that leverages artificial intelligence technology. This study presents a method for creating models according to the CPC classification model based on the KorPatBERT(Korean Patent BERT) that can deeply understand the detailed technical context of patent documents through pre-training involving vast patent data. Furthermore, this study presents a method for generating high-dimensional document embedding vectors that can effectively reflect the technical subject and context of patent documents and a method for building a search system capable of processing large volumes of patent data in real time. By integrating the proposed patent search model into this system, the study successfully demonstrated improved search performance compared with existing methods in objective performance evaluations. This study can contribute toward enhancing industrial applicability and practical usability by applying the processes of currently operational patent search data and systems. The current study’s findings are expected to provide a foundation for nations and companies to continuously lead innovation and efficiently manage and utilize patents.